Efficiency and bacterial populations related to pollutant removal in an upflow microaerobic sludge reactor treating manure-free piggery wastewater with low COD/TN ratio. (February 2016) - Meng, Jia; Li, Jiuling; Li, Jianzheng; Sun, Kai; Antwi, Philip; Deng, Kaiwen; Wang, Cheng; Buelna, Gerardo
Highlights: An upflow microaerobic sludge reactor used to treat manure-free piggery wastewater. NH4 + -N and COD/TN ratio of the wastewater being 299 mg/L and 0.84, respectively. Average load removal of COD and TN as high as 0.72 and 0.94 kg/(m 3  d), respectively. Aerobes, anaerobes and facultative aerobes thriving in the microaerobic system. Populations related to COD, NH4 + -N, TN and phosphate removal being identified. Abstract: A novel upflow microaerobic sludge reactor (UMSR) had proved excellent in nitrogen removal from manure-free piggery wastewater characterized by high concentration of ammonium (NH4 + -N) and low chemical oxygen demand (COD) to total nitrogen (TN) ratio, but the biological mechanism in the UMSR was still indeterminate. With a constant nitrogen loading rate of 1.10 kg/(m 3  d) at hydraulic retention time 8 h, the UMSR was kept performing for 67 days in the present research and the average load removal of COD, NH4 + -N and TN was as high as 0.72, 0.76 and 0.94 kg/(m 3  d), respectively. Compared with the inoculated sludge, the acclimated sludge was richer in genera responsible for the biological removal of carbon, nitrogen and phosphorus. Ammonium oxidation bacteria, heterotrophic denitrifiers, autotrophic denitrifiers and phosphate accumulating organisms coexisted perfectly in the microaerobic system, and their synergistic action made the UMSR perform well in COD, NH4 + -N, TN and phosphate removal.